Adherence to healthy ways of life through counselling by health care professionals - Toledo, Mariana Tamara Teixeira de; Abreu, Mery Natali; Lopes, Aline Cristine Souza (Revista de Saúde Pública, 2013)
OBJECTIVE: To estimate the prevalence of factors associated with adherence to healthy ways of life. METHODS: This is a cross-sectional study carried out with users aged over19 from a primary health care unit in Belo Horizonte, MG, Southeastern Brazil, from 2009 to 2010. The sample was selected to estimate the proportion of people who adhere to healthy ways of life (healthy eating and physical activity) through counseling conducted by health care professionals, and associated socio-demographic, dietary and health factors. Additionally, the perceived benefits from the adherence to healthy ways of life and their possible barriers were verified. Descriptive analysis, univariate (Chi-square Test or Fisher's Exact) and multivariate by Poisson Regression were performed. RESULTS: Of the 417 users selected for the survey, only 40.8% received counseling, of which 50.9% demonstrated adherence. In multivariate Poisson regression, adherence was associated with the perception of food being healthy (PR = 1.67, 95%CI 1.15;2.43) and participation in the public service health campaigns(PR = 1.55, 95%CI 1.18;2.03). The main reported benefits of adherence were greater willingness and weight loss and, the most commonly reported barriers were difficulty of changing habits and lack of time. CONCLUSIONS: Adopting healthier lifestyles requires the proposing of strategies that promote adherence, as well as the participation of professionals in implementing counseling as a health promoting action that generates greater autonomy and quality of life among those involved, supported by policies and programs promoting health.